Luces y Sombras: El Rol del Derecho Civil en el Siglo XXI - Fernández Sessarego, Carlos Ricardo (2020)
DOI: 10.26439/advocatus2018.n036.4734 On this occasion, ADVOCATUS had the opportunity to interview Carlos Fernández Sessarego, author of the first book of the Civil Code, a mandatory reference in the exercise of Civil Law, and co-author of the Three-Dimensional Theory. Throughout the following interview, an analysis is offered regarding the role of Civil Law in the 21st century, addressing the detachment of the patrimonialist French tradition, and the change towards a more humanistic Civil Law, alongside its implications, specifically, the damage to the person. Finally, the validity of the Civil Code of 1984 is analyzed, including its shadows.